2015
DOI: 10.2174/1874944501508010035
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet: Socio-cultural Relevance for Contemporary Health Promotion

Abstract: Abstract:In biomedical literature, The Mediterranean Diet describes a healthy eating model, based on epidemiological findings on the predominant eating practices in Crete and Southern Italy in the 1960s. At the time, the level of life expectancy in this region was amongst the highest worldwide and rates of cardiovascular disease were amongst the lowest. Medical research has since given increasing attention to this dietary pattern and its potential health benefits. The various components of The Mediterranean Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…Stated differently, heterophily in social networks may be crucial to changing meat consumption habits. As has suggested, focusing on socio-cultural aspects of food and eating may be an avenue worthy of further investigation for dietary interventions [9]. The results of this study further support this idea.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Stated differently, heterophily in social networks may be crucial to changing meat consumption habits. As has suggested, focusing on socio-cultural aspects of food and eating may be an avenue worthy of further investigation for dietary interventions [9]. The results of this study further support this idea.…”
Section: Discussionsupporting
confidence: 78%
“…It is also important to know the demographics of convinced meat eaters to target specific groups in health promotion initiatives [5]. Furthermore, this also enables us to explore some pathways that could be used in future interventions aimed at encouraging meat-reduced diets, as it has been suggested that a focus on the social environment of food consumption may be more successful as compared to a focus on diet and health directly [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be explained by the greater association found in this sex for the ego-oriented motivational climate, which would imply a greater care of the diet for the improvement of the physical fitness for competition and physical attractiveness [36,61]. In addition, MD was inversely associated with tobacco consumption in men, which could demonstrate that to follow an appropriate diet could help to prevent the consumption of this substance, as shown by Phull et al [62]. In this line, adherence to MD was positively related to self-concept, especially in women.…”
Section: Discussionmentioning
confidence: 87%